2011
DOI: 10.5430/wje.v1n2p3
|View full text |Cite
|
Sign up to set email alerts
|

Management of Group Work as a Classroom Activity

Abstract: Students appreciate group work as a means of learning and several studies also suggest that students who work together in groups have better learning outcomes. Nevertheless, teachers still seem reluctant to use group work as a pedagogical tool in the classroom.The main focus of this qualitative study is to address group work as a classroom activity from the teachers' perspectives, and more specifically to ascertain why teachers are reluctant to use group work as a mode of working in education.Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 34 publications
0
24
0
2
Order By: Relevance
“…The data this text draws upon originates from an extensive study intended to develop knowledge of teachers' experiences with group work as a pedagogical mode in educational settings (Hammar Chiriac & Forslund Frykedal, 2011). Data collection was accomplished by means of three focus groups with a total of 11 teachers who educated students ages 11-16 years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data this text draws upon originates from an extensive study intended to develop knowledge of teachers' experiences with group work as a pedagogical mode in educational settings (Hammar Chiriac & Forslund Frykedal, 2011). Data collection was accomplished by means of three focus groups with a total of 11 teachers who educated students ages 11-16 years.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous article (Hammar Chiriac & Forslund Frykedal, 2011) we have shown that the concepts of leadership and teachership introduced by Granström (2007) could be beneficial to but are not sufficient for a profound understanding of group work management in the classroom. By employing symbolic interactionism (SI) as a complementary theoretical perspective (Blumer, 1969;Charon, 2006) it was possible to discover how teachers' takenfor-granted unreflective ideas affect their acts.…”
Section: Presumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recently completed study, teachers clearly demonstrated that they primarily expect the students to develop the ability to collaborate, and thereby use group work as an object, and not principally to acquire subject knowledge, during group work (Hammar Chiriac & Forslund Frykedal, 2011). …”
Section: Introductionmentioning
confidence: 99%